2023
DOI: 10.1021/acssuschemeng.3c00141
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Life Cycle Assessment of Lithium-Sulfur Batteries for Stationary Energy Storage

Abstract: The lithium-sulfur (Li-S) battery represents a promising next-generation battery technology because it can reach high energy densities without containing any rare metals besides lithium. These aspects could give Li-S batteries a vantage point from an environmental and resource perspective as compared to lithium-ion batteries (LIBs). Whereas LIBs are currently produced at a large scale, Li-S batteries are not. Therefore, prospective life cycle assessment (LCA) was used to assess the environmental and resource s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Due to the high demand for batteries, the lithium-sulfur (Li-S) battery emerges as a promising next-generation technology due to its potential for high energy densities without rare metal inclusion, offering environmental and resource advantages over lithium-ion batteries (LIBs) [151]. While LIBs are currently mass-produced, Li-S batteries are not, prompting a prospective life cycle assessment (LCA) to evaluate their environmental and resource impacts under various scenarios.…”
Section: Identification Of Gaps In Current Research and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high demand for batteries, the lithium-sulfur (Li-S) battery emerges as a promising next-generation technology due to its potential for high energy densities without rare metal inclusion, offering environmental and resource advantages over lithium-ion batteries (LIBs) [151]. While LIBs are currently mass-produced, Li-S batteries are not, prompting a prospective life cycle assessment (LCA) to evaluate their environmental and resource impacts under various scenarios.…”
Section: Identification Of Gaps In Current Research and Technologymentioning
confidence: 99%
“…While LIBs are currently mass-produced, Li-S batteries are not, prompting a prospective life cycle assessment (LCA) to evaluate their environmental and resource impacts under various scenarios. According to Wickerts et al [151] the Li-S batteries has a lower carbon footprint associate with their production and use, lower environmental impact across life-cycle, and high potential benefits for used as a stationary energy due its high energy density and efficiency but challenges such as durability and long-term stability of Li-S batteries, as well as to improve manufacturing and recycling processes to further reduce their environmental impact [151]. Freitas et al [152] relationship between academics, stakeholders, and policymakers is essential to success, not only on technological advancements and economic regulations but also on user acceptance, which remains an underexplored aspect.…”
Section: Identification Of Gaps In Current Research and Technologymentioning
confidence: 99%
“…It was also indicated that the environmental performance of SSBs could be increased by coating the active cathode material with Lithium Niobate using the Atomic Layer Deposition (ALD) and Physical Vapor Deposition (PVD) techniques. Wickerts' [81] study focused on the application of SSBs for energy storage purposes and analyzed six different scenarios with LiTFSI as the electrolyte and found that the electricity source, life cycle of the batteries, and the specific energy density are the key parameters to reduce the environmental impacts. They considered different electricity mixtures (low intensity, medium intensity, and high intensity) with a scope of both cradle-to-gate and cradle-to-grave, considering the end of the life of LIS.…”
Section: Life Cycle Assessment Of Emerging Batteries For Automobiles ...mentioning
confidence: 99%
“…There is a growing understanding that the research and development of new clean energy sources is crucial because of the increasing consumption and depletion of nonrenewable resources on earth. In the 21st century, secondary batteries are favored as one of the most mature energy storage technologies. Among them, rechargeable lithium-ion batteries (LIBs) are the most prominent and widely used. Unfortunately, high-energy-density Li metal batteries suffer from the issue of lithium dendrites that will pierce the diaphragm, triggering the short-circuiting or even an explosion of the battery. The issue has grown to be a significant barrier to the continued advancement of Li batteries. Magnesium metal is regarded as an ideal anode material for multivalent batteries because of its various intrinsic ascendancy: abundant reserves, low cost, high volumetric capacity (Mg 3833 mAh cm –3 vs Li 2062 mAh cm –3 ), and high security due to rare dendritic deposition. Therefore, rechargeable magnesium batteries (RMBs) are considered as a new generation of energy products to assist or replace the LIBs.…”
Section: Introductionmentioning
confidence: 99%